A clinicopathological study of malignant melanoma with special reference to atypical presentation - Mukhopadhyay Subhalakshmi; Ghosh Sambuddha; Siddhartha Dutta; Mitra Pradip (Wolters Kluwer Medknow Publications, 2008)
Malignant melanoma is a tumor of melanocytic origin. Lymphatic and hematogenous metastases are common in this condition. Retrospective analysis was performed in 16 consecutive cases diagnosed histopathologically as malignant melanoma at the pathology department of a medial college in eastern India. 75% of the patients were male; majority of them was in their sixth decade. All (100%) the lesions were pigmented. The primary site was known in all cases, except two (12.5%). Out of the 14 cases with known primary site 11 (78.57%) were cutaneous melanomas, including one arising in labia minora, two (14.29%) were ocular and one (7.14%) was vaginal in origin. Among cutaneous melanomas, superficial spreading type was the commonest variety and mixed population of epithelioid and spindle cell was the commonest histopathological pattern. The commonest grade of invasion was grade III (Clark′s). The clinical presentation of the case of vaginal melanoma and the two cases of secondary melanomas, including the one with obscure primary tumor, were bewildering and hence are discussed separately.